2020
DOI: 10.1186/s13045-020-00945-8
|View full text |Cite
|
Sign up to set email alerts
|

Principles and innovative technologies for decrypting noncoding RNAs: from discovery and functional prediction to clinical application

Abstract: Noncoding RNAs (ncRNAs) are a large segment of the transcriptome that do not have apparent protein-coding roles, but they have been verified to play important roles in diverse biological processes, including disease pathogenesis. With the development of innovative technologies, an increasing number of novel ncRNAs have been uncovered; information about their prominent tissue-specific expression patterns, various interaction networks, and subcellular locations will undoubtedly enhance our understanding of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 235 publications
(434 reference statements)
1
55
0
Order By: Relevance
“…There have been many efforts in the development of computational tools and high-throughput sequencing technologies, such as RNA capture sequencing (RNA CaptureSeq), whole-genome tiling arrays, the lncRNA microarray technique, serial expression of gene expression (SAGE), the expressed sequence tag (EST) method, and RNA-sequencing (RNA-seq). More than half a million lncRNA transcripts have been predicted in silico to understand their biological mechanisms [ 49 ]. Accumulating evidence suggests that lncRNAs are emerging regulators of diverse biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many efforts in the development of computational tools and high-throughput sequencing technologies, such as RNA capture sequencing (RNA CaptureSeq), whole-genome tiling arrays, the lncRNA microarray technique, serial expression of gene expression (SAGE), the expressed sequence tag (EST) method, and RNA-sequencing (RNA-seq). More than half a million lncRNA transcripts have been predicted in silico to understand their biological mechanisms [ 49 ]. Accumulating evidence suggests that lncRNAs are emerging regulators of diverse biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a mounting body of evidence supporting the physiological relevance of ncRNAs, most studies performed to date have focused primarily on proteins themselves or deciphering the pathways associated with annotated ncRNAs. Moreover, due to the perceived insurmountability of the sheer amount of data generated by NGS/TGS analyses, the full extent of regulatory networks created by ncRNAs often gets overlooked (68). In addition, whereas the cost of RNA-seq is now reasonable for most active research programs, tools necessary for the interpretation of these sequencing datasets typically require significant computational expertise and resources markedly hindering widespread utilization of these tools.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs constitute a class of noncoding RNA molecules with powerful gene regulation potential. They bind to complementary target mRNAs, resulting in mRNA translational inhibition or degradation [ 137 ]. Notably, seven miRNAs have been found that directly target m6A methyltransferases in diseases (Fig.…”
Section: Targeting M6a Methyltransferase By Ncrnamentioning
confidence: 99%